(untitled) (Annals of Bangladesh Agriculture, 2020)
This experiment was conducted to determine the pathology of pullorum disease of chickens and molecular identification of its pathogen. A total of 108 samples, including swabs from different organs were collected from different commercial layer farms of Gazipur district. The histopathological samples were collected in 10% formalin and the swabs were collected in tetrathionate broth. Samples were subjected to isolation and identification of the causal agent followed by gross and histopathological study of the affected visceral organs. Fifty eight out of 108 cloacal swabs (53.7%) were Salmonella positive. The percentage of Salmonella positive in liver swabs, spleen swabs, lung swabs and intestinal swabs from dead birds were 55.88%, 32.35%, 35.29% and 47.05%, respectively. On average, 52.94% livers of Salmonella affected birds were enlarged, congested and hemorrhagic and necrotic foci was present in 32.35% liver. Unabsorbed and coagulated yolk was found in 70.58% cases. From these 38.24% spleens were swollen and congested and 44.12 % kidneys were enlarged. At histopathology, 52.94% livers showed congestion, focal necrosis with multifocal infiltration of histiocytes in liver parenchyma. Focal necrosis and inflammatory cells were found in 70.58% spleen. Infiltration of heterophils in intestinal mucosa was found in 47.05% cases. 20.58% (7 out of 34) samples were PCR positive for Salmonella Pullorum organism. Ann. Bangladesh Agric. (2019) 23(1) : 25-35